Analysis of Performance of Permanent Magnet Generator Fluks Axial 1 Phasa with Variation Load - Saleh, Zulkiffli; Apriani, Yosi; Karim, Khoirul; Aldiansyah, Aldiansyah (Journal of Robotics and Control (JRC), 2021)
With the potential of low water head energy and relatively small water discharge then it takes a low round generator to be applied to the potential of existing energy. The development of Permanent Magnet Generator (PMG), being an alternative considering the pole construction of the rotor is relatively simple compared to conventional generators, so it is technically required a more number of rotor poles in the effort to lower the speed The nominal dial generator. The purpose of this research is to analyze the 1-phase axial generator performance with varied resistive loads and inductive loads. This research has 4 stages of research: 1). Study literature.Â  2). Carried out testing tools. 3). Measurement of data retrieval.Â  4). Data analysis. From this research obtained results from the tools and measurements of the data retrieval of the performance of axial generator 1 phase with inductive and resistive load Vaiasi. Load mounted 15 watts, voltage 35.10, current 0.80, RPM 2550 when load 75 Waat, Voltage 11.50, current 1.54, RPM 2220. From these results can be concluded axial generator 1 phase currents also get bigger but voltage and rpm decreases.